Improving safety culture in the company based on attitudes and behavior of its employees - Anna Gembalska-Kwiecien (Institute of Economic Research (IER), 2017)
Research background: The paper presents basic issues related to safety culture. Moreover, there can be found an information about the factors determining the desirable and undesirable, as well as the good and bad safety culture, and the most important knowledge concerning its shaping. The empirical part presents the studies on the impact of attitudes and behavior of employees on the development of safety culture. Elements were tested such as: environment and working conditions, and behaviors and attitudes of employees. Purpose of the article:The aim of the study was to analyze attitudes and behaviors of employees and their impact on shaping the safety culture in a given company.The learning goal of the project was an introduction to the opinion of surveyed employees about work safety culture in the company. The utilitarian aim of the study was to draw attention to the need of taking action to influenceattitudes and behavior of employees onshaping the areas of work safety culture in order to improve safety culture and thereby improve safety in the company. Methodology/methods:Research tools were: interview, documentation analysis and anonymous survey of company employees. Findings& Value added:The study shows that the majority of employees act in accordance withrules and try not to take risky actions, they also feel responsible for the safety of themselves and their co-workers, the environment and working conditions are in line with legal requirements, and accidents rarely occur. In the surveyed company the safety culture is high, which is proven by features such as: a sense of personal responsibility of each employee for safety matters, lack of acceptance for people taking risky behavior, compliance with health and safety regulations and appreciation of their validity - those are most frequently mentioned features of performance of high culture safety in workplace.
Keywords: I1; D2; A3; L2; 330; safety management; organizational culture; safety culture; human factor; working environment